Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Explore thousands of questions and answers from knowledgeable experts in various fields on our Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

f(x) = 3x - 3
g(x) = 4x + 5

find (f+g) (3)


Sagot :

Answer:

23

Step-by-step explanation:

(f + g)(3) = f(3) + g(3)

f(3) = 3(3) - 3 = 9 - 3 = 6

g(3) = 4(3) + 5 = 12 + 5 = 17

Then

(f + g)(3) = 6 + 17 = 23

Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.